Knowledge about Danger Signs of Obstetric Complications and Associated Factors among Postnatal Mothers of Mechekel District Health Centers, East Gojjam Zone, Northwest Ethiopia, 2014 - Gedefa Amenu; Zerfu Mulaw; Tewodros Seyoum; Hinsermu Bayu (Scientifica)
Background. Developing countries like Ethiopia contributed highest level of maternal mortality due to obstetric complications. Women awareness of obstetric danger sign to recognize complications to seek medical care early is the first intervention in an effort to decrease maternal death. Objective. To assess knowledge about danger signs of obstetric complications and associated factors among postnatal mothers at Mechekel district health centers, East Gojjam zone, Northwest Ethiopia, 2014. Methods. An institution based cross-sectional study was conducted from August to October, 2014, in Mechekel district health centers. Systematic random sampling was used to select four hundred eleven study participants. A pretested structured questionnaire was used to collect data. Data were entered to Epi Info version 3.5.3 and exported to SPSS 20.0 for further analysis. Descriptive and summary statistics were done. Logistic regression analyses were used to see the association of different variables. Odds ratios and 95% confidence interval were computed to determine the presence and strength of association. Results. According to this study, 55.1% participants were knowledgeable about danger signs of obstetric complications. Maternal and husband educational level ((AOR = 1.977, 95% CI: 1.052, 3.716) and (AOR = 3.163, 95% CI: 1.860, 5.3770), resp.), family monthly income ≥ 1500 (AOR = 2.954, 95% CI: 1.289, 6.770), being multipara (AOR = 7.463, 95% CI: 1.301, 12.800), ANC follow-up during last pregnancy (AOR = 2.184, 95% CI: 1.137, 4.196), and place of last delivery (AOR = 1.955, 95% CI: 1.214, 3.150) were variables found to be significantly associated with women’s knowledge on danger signs of obstetric complications. Conclusion. Significant proportion of respondents were not knowledgeable about obstetric danger signs and factors like educational status, place of last delivery, and antenatal follow-up were found to be associated.